Pengelolaan Corporate Social Responsibility (CSR) Pada Program The Gade Clean And Gold Sebagai Upaya Meningkatkan Pendapatan Masyarakat Dengan Mengurangi Sampah Di Kota Ambon: (Studi Kasus Pada PT. Pegadaian Kantor Area Ambon) - Basuki, Ferry Hendro; Liptiay , Janes R (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Social and environmental issues have gained attention from business actors due to their potential impact on the environmental ecosystem and the company's image in the eyes of investors. Corporate Social Responsibility (CSR) is a company's commitment to creating a positive impact on the environment and the surrounding community. High waste production and lack of coordination in waste management have led to serious health and environmental problems. This study aims to understand the planning, implementation, and effectiveness of The Gade Clean and Gold Program. This research uses a qualitative method with a case study approach. Data collection is done through interviews, observations, and documentation. The data analysis methods used are data reduction, data presentation, and drawing conclusions. Triangulation is used to test the validity of the data. Based on the research results, program planning focuses on empowering and educating the community to be environmentally conscious. In the program implementation, the lack of communication regarding facilities and infrastructure, as well as the absence of a well-structured organization in the waste bank, hinder operational activities. The effectiveness of the program creates positive awareness among the community regarding waste management, and the benefits of waste separation can increase income through gold savings. Keyword: Green Economy,CSR Management,The Gade Clean and Gold, Income